Pengaruh Fee Audit, Independensi Dan Profesionalisme Auditor Terhadap Kualitas Audit Di KAP Provinsi Bali - Desak Ayu Gita Padma Wedari; Ni Komang Sumadi (UNHI Press, 2023)
Issues regarding audit quality related to the implementation of the correct application of audit standards by auditors have become a public discussion in recent years. The cause of this phenomenon is identified by the existence of a biased assessment of the independence and professionalism of the auditor which is not fully interpreted by the client as well as negotiations at the beginning of the employment contract regarding the amount of audit fee received by the auditor, which is also considered to have an effect on the quality of the audit process produced by the auditor. The purpose of the study was to determine the effect of audit fees, independence and professionalism on the quality of the audit process. A public accounting firm in Bali that is registered as a member of IAPI was chosen as the research location with auditors as the sample. The number of samples used in the data analysis is 93 samples. Data collection using a questionnaire (questionnaire) and multiple linear regression analysis was used as an analytical technique. The results of data processing show that audit fees, independence, and professionalism have a positive and significant effect on the quality of the audit process either simultaneously or partially. Keywords: amount of audit fee, independence, professionalism, audit quality.